Visceral leishmaniasis escaping the diagnosis and withstanding treatment in a case of recurrent pyrexia - Gulati, Shipra; Dessai, Rishikesh; Patnaik, Nikhil K.; Chawla, Kunal (International Journal of Research in Medical Sciences, 2023)
Though visceral leishmaniasis (VL) is the leading parasitic infection causing deatharound the world after malaria, it is a less suspected cause of pyrexia of unknown origin (PUO). We present a case of a middle aged man who was diagnosed with VL only months later owing to the stealthily masquerading disease as also to a generally low index of suspicion for it. A 59-year-old from Uttarakhand presented to us with complaint of fever of a few weeks duration. He was found to have a bicytopenia with elevated liver enzymes. Routine imaging studies were non-contributory. Cultures revealed candidemia while tests for viral and other atypical infections were negative. A bone marrow examination (BME) revealed haemophagocytosis. Positron emission tomography–computed tomography (PET-CT) showed mildly FDG avid hepatosplenomegaly. He was treated as a case of candidiasis with secondary hemophagocytic lymphohistiocytosis (HLH) and was discharged. He was readmitted months later with recurring fever. Repeat investigations revealed pancytopenia with marked hepatosplenomegaly. A repeat BME, however, revealed Leishmania donovani (LD) bodies. Patient was treated with liposomal amphotericin B (LAmB) and discharged. Though the patient’s symptoms improved soon after, he was again admitted a couple of months later and found to have VL persisting in the BM aspirate. This report underscores the need to extensively evaluate cases of PUO rather than summarily dismissing them as routine. VL is one of the less suspected etiologies despite being the second largest parasitic killer.